Urodynamic evaluation of patients with localized prostate cancer before and 4 months after robotic radical prostatectomy - Dong Sup Lee (Nature Portfolio, 2021)
Abstract Radical prostatectomy can alter the anatomy of the urinary bladder. We aimed to evaluate bladder function before and 4 months after radical prostatectomy using the urodynamic test and overactive bladder (OAB) symptom score. Among 70 prospectively enrolled patients, 61 patients completed the study. In the urodynamic test, bladder capacity and compliance did not change, the frequency of involuntary detrusor contraction decreased, the maximum flow rate and bladder outlet obstruction index improved, and the maximum urethral closure pressure (MUCP) deteriorated. Further evaluation of urodynamic parameters according to changes in symptoms was made. Although change in bladder compliance was correlated with changes in OAB symptoms, not the relative change of bladder compliance but the relative change in the MUCP was reliable factor when OAB symptoms were deteriorated. In general, prostatectomy did not deteriorate the condition of the detrusor; rather, change in the MUCP could be responsible for postprostatectomy OAB.